Brief report: A randomized controlled trial examining peer support and behavioral weight loss treatment. (October 2015) - Kulik, Noel; Ennett, Susan T.; Ward, Dianne S.; Bowling, J. Michael; Fisher, Edwin B.; Tate, Deborah F.
Abstract: Peer support among adolescents has been positively associated with heath behaviors; however, enhancing peer support for weight loss has rarely been studied among adolescents. This study examined whether a peer support training component delivered to enhance a standard weight loss program led to improved outcomes. Forty-one overweight adolescent females were randomly assigned to a Standard or Enhanced Peer Support intervention. The Enhanced group received in person peer support skills training and practiced skills using social networking. At 16 weeks, participants in the Enhanced condition reported significantly increased perceptions of friend support. Both groups demonstrated significant weight loss (6.4 lbs, ± 8.3). Attendance and self-monitoring were associated with weight loss. Perceptions of peer support can be increased with a peer training component, but did not increase weight loss during the short term.